(untitled) (Applied Biological Research, 2015)
The present study was aimed to elucidate the ameliorative effect of vitamin C on biochemical alterations in broilers treated with lead acetate. One hundred and eight (1 day old) broiler chicks were reared for 2 weeks and randomly divided into 6 equal groups. Group I birds served as control. Group II and III birds were given lead acetate @ 250 and 500 ppm, respectively, while group IV and V were supplemented with vitamin C @ 40 mg L-1 water in addition to lead acetate @ 250 and 500 ppm, respectively. Group VI birds were supplemented with vitamin C @ 40 mg L-1 water in their normal feed. Total serum protein analysis revealed a significant decrease in lead treated birds while as AST, ALT, blood urea nitrogen (BUN), creatnine and uric acid revealed a significant increase but the values were modulated in vitamin C supplemented birds.